Libertad para competir en el mercado: recursos, procesos y resultados - Iguíñiz Echeverria, Javier María (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
Freedom to compete in the market: resources, processes, and resultsHerein we analyze three concepts of market competition. Although the different aspects of freedom can be appreciated in each one of them, they make an especial contribution to some of them. We propose that the ‘neoclassical general equilibrium’ chiefly contributes to the discussion of the outcomes of an economic activity; the ‘barriers to entry’ approach calls for a study of the resources necessary to compete; and the ‘competition as a process’ approach emphasizes the competitive activity itself. Moreover, as we move from the first onwards, enriching the meaning of competition, the possibility of losing opportunities to participate in the market becomes more evident. Entry and exit are part of the competitive process. Each concept of competition responds to theories that specify or allude to certain types and distribution of economic agents’ freedoms to manoeuvre. Throughout this study, we often quote Amartya Sen with the purpose of buildingbridges between the study of competition and the approach of ‘development as freedom.

Analizamos tres conceptos de competencia en el mercado. Aunque en cada uno de ellos se pueden apreciar las distintas facetas de la libertad, también aportan especialmente a alguna de ellas. Proponemos que el enfoque de «equilibrio general neoclásico» aporta principalmente a la discusión de los resultados de una actividad económica, el enfoque de las «barreras a la entrada» invita a estudiar los recursos necesarios para competir y el enfoque de la «competencia como proceso» pone el acento en la actividad competitiva misma. Además, conforme nos movemos del primero hacia los demás, enriqueciendo el significado de la competencia, se pone más en evidencia la existencia de pérdidas de oportunidades para participar en el mercado que provienen de la propia competencia económica. Cada concepto de competencia responde a teorías que especifican o aluden a ciertos tipos y distribución de márgenes de acción y de acceso a herramientas para competir. En todo el trabajo citamos a menudo a Amartya Sen con el fin de establecer puentes entre el estudio de la competencia y el enfoque del «desarrollo como libertad»
Keywords: Capacidades; Competencia; Desarrollo Humano; Instituciones; Libertad Económica; https://purl.org/pe-repo/ocde/ford#5.02.01